Strengthening Teacher Support and Adolescent Self-Efficacy Through the Teenager Care Method in Preventing Early Marriage - Putu Sudewi Arsini; Dewi Kartika Sari; Diadjeng Setya Wardani; I Wayan Agung Indrawan; Sri Andarini; Agus Adi Putrawan (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Indonesia is the country with the second-highest ranking in terms of child marriage. One preventive approach is to enhance teacher support and adolescent self-efficacy by utilizing innovative learning methods. This study aims to analyze the effect of the Teenager Care Method on improving teacher support and students' self-efficacy in preventing early marriage. This study used a quasi-experimental one-group pretest-posttest design. This research was conducted at Singosari State Junior High School. From a total population of 50 teachers and 250 students who met the inclusion and exclusion criteria, 44 teachers and 72 students were used as research samples. This research was conducted at one of the junior high schools in Singosari. The first involved the method for teachers, implemented through lectures, interactive dialogues, and role-play. The second intervention targeted adolescents and was conducted using lecture-based methods and small-group case discussions. This study utilizes IBM SPSS Statistics 26 software with a 95% confidence level. The significance limit value of alha is 0.05. Data were analyzed using the Wilcoxon Signed-Rank Test. The results showed a significant increase in teacher support for early marriage prevention after the implementation of the Teenager Care Method (p < 0.001). Similarly, there was a substantial improvement in students' self-efficacy regarding the prevention of early marriage (p < 0.001). The Teenager Care method effectively enhances teacher support and students' self-efficacy in preventing early marriage. This method could be a practical preventive strategy that involves active teacher participation and fosters adolescent empowerment.Keywords: Teacher Support, Self-Efficacy, Adolescents, Early Marriage